(untitled) - Fernanda Machado Taveira; Antônio Lúcio Teixeira; Renan Barros Domingues (Arquivos de Neuro-Psiquiatria)
The present study aimed at evaluating respiratory parameters in multiple sclerosis (MS). The sample comprised 30 patients with MS diagnosis and 30 healthy subjects, matched by gender and age. Neurological assessment, expanded disability status scale (EDSS), manovacuometry, and peak flow (PEF) were performed. Patients with MS had lower values of maximum inspiratory (MIP) and expiratory (MEP) pressures and PEF compared to healthy controls. It was shown that respiratory impairment may be present in MS patients with low functional disability by EDSS. The data suggest that manovacuometry and PEF determination should be carried out systematically in patients with MS, and may be a reliable tool for the early detection of respiratory impairment allowing early respiratory rehabilitation.